Atheism in Pakistan: Influences and challenges amongst Muslim youth - Faisal, Muhammad Adnan (2022)
Atheism is a growing socio-religious phenomenon across the world; however, its understanding, forms, influencing factors, and the challenges it has produced are varied from one social context to another. As atheism is also growing in Pakistani society, this study is an attempt to explore the forms of atheism, factors behind its spread, and the challenges it has produced for the Muslim youth of Lahore, Pakistan. This research is significant to comprehend the arguments offered to alienate the youth from their religion, and to initiate a way forward to encounter atheism. This study focuses on answering the basic question as to what are the forms, influencing factors, and the challenges the Muslim youth of Lahore are exposed to deviate from their belief in the behests of Islam, their religion at birth. The researcher has used Semi-structured qualitative interviews as a method for the current study and 19 self-identified atheists ranging from their diverse educational, institutional, and bents of mind and 14 religious scholars have been interviewed on the bases of comprehensive open-ended questionnaire. A non-probability snow-ball sampling technique has been used for the selection of the participants for interviews. Each interview has been recorded, transcribed, and the data has been interpreted to realize the argument in the participants’ responses. This study concludes that Muslim youth of Lahore equate atheism with liberty and freedom of life and are following implicit atheism, a form of atheism. It has also been concluded that the factors which led the Muslim youth of Lahore towards atheism as based on social, intellectual, or emotional dimensions. Moreover, it has also been figured out the challenges which have been produced by atheism include morality without religion, religious laws, and unaccountable sense of liberty. In conclusion, the major findings suggest that the debate of atheism is highly contextual and adaptation of research methodologies from context to context should be done; therefore, the results of the study in hand cannot be over-generalized.